Illocutionary Speech Acts and Moral Values on “Jihadul Muhibbin”: A Pragmatics Study - Machmudatul Arifin (Islah: Journal of Islamic Literature and History, 2021)
This research aims to describe the forms of illocutionary speech acts on a novel entitled Jihadul Muhibbin and to explain the moral values on it. This study uses a qualitative descriptive method by doing some steps including taking notes of utterances in the novel and classifying the forms of illocutionary speech acts based on Searle's theory (1969). Searle divides illocutionary speech acts into five types including representative, directive, commissive, expressive, and declarative. In addition, the researcher also tries to identify what moral values are contained in the novel Jihadul Muhibbin. The results showed that the forms of illocutionary speech acts contained in the novel Jihadul Muhibbin have various types including representative (88 occurrences), Commissive (4 occurrences), directive (51 occurrences), expressive (6 occurrences), and declarative (9 occurrences). Furthermore, the moral values contained in the novel Jihadul Muhibbin there are two types including good moral values and bad moral values.